1995
DOI: 10.1113/expphysiol.1995.sp003910
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to glomerular injury in the diabetic biobreeding rat

Abstract: SUMMARYThis study was designed to determine whether the diabetic BioBreeding rat develops significant renal injury following long-term moderate to severe hyperglycaemia. Diabetic and control rats were followed from the onset of diabetes (2-4 months) to 18 months of age. Frank proteinuria and/or albuminuria were always absent. Glomerular filtration rate, measured by inulin clearance (ml min-' (100 g body weight)-1), was significantly higher in diabetic rats than in controls at 10, 12 and 18 months of age. Advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…animal types showed substantial increases in GBM thickness with age, and these data were consistent with several studies that indicated this parameter was a reliable biomarker of aging in rats (Yagahashi et al, 1978;Cohen et al, 1987;Feld et al, 1995). Our morphometric data also showed that GBMs in BB/DP h animals were significantly thicker than age-matched BB/DR controls at 3 months, 6 months, and 1 year postonset of hyperglycemia.…”
Section: Gbm Morphometry Morphometric Analyses Of Allsupporting
confidence: 91%
See 4 more Smart Citations
“…animal types showed substantial increases in GBM thickness with age, and these data were consistent with several studies that indicated this parameter was a reliable biomarker of aging in rats (Yagahashi et al, 1978;Cohen et al, 1987;Feld et al, 1995). Our morphometric data also showed that GBMs in BB/DP h animals were significantly thicker than age-matched BB/DR controls at 3 months, 6 months, and 1 year postonset of hyperglycemia.…”
Section: Gbm Morphometry Morphometric Analyses Of Allsupporting
confidence: 91%
“…Our morphometric data also showed that GBMs in BB/DP h animals were significantly thicker than age-matched BB/DR controls at 3 months, 6 months, and 1 year postonset of hyperglycemia. This was also not unexpected as other investigators showed that as early as 6 months postonset of hyperglycemia, GBMs in BB/DP rats were thicker than age-matched BB/DR rats (Brown et al, 1983;Cohen et al, 1987;Chakrabarti and Sima, 1989;Feld et al, 1995). Also, Feld et al (1995) showed that at 1 year, GBMs were 25% wider in BB/DP rats than in age-matched BB/DR controls.…”
Section: Gbm Morphometry Morphometric Analyses Of Allsupporting
confidence: 59%
See 3 more Smart Citations